The winning weapon : the atomic bomb in the Cold War, 1945-1950 : with a new preface - Herken, Gregg, 1947- (Princeton legacy library., 1988)
This book makes clear how, and why, after World War II American diplomats tried to make the atom bomb a winning weapon, "" an absolute advantage in negotiations with the Soviet Union. But this policy failed utterly in the 1948 Berlin crisis, and at home the State Department opposed those scientists who advocated international cooperation on nuclear matters. Originally published in 1988. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press.